Optimization of plastic polymers for shellfish aquaculture infrastructures: in situ antifouling performance assessment - Freitas, Vânia; Gonçalves, Odete; Dolbeth, Marina; Ramos, Sandra; Morais, João; Ozorio, Rodrigo O. de A.; Martins, Irene; Almeida, Joana R. (Frontiers in Marine Science, 2023)
Biofouling poses a significant challenge to bivalve aquaculture affecting both the target culture and/or the immersed infrastructure. In suspended bivalve cultures (e.g., oysters and scallops), biofouling accumulation leads to additional labor demands and increased costs for the maintenance of underwater structures. Given that the inherent properties of materials used in farming infrastructure influence the formation of fouling communities, evaluating how these materials perform under diverse environmental conditions can help the industry select the most effective materials for preventing or minimizing biofouling growth. This study evaluates the impact of aquaculture material and environmental conditions on biofouling, focusing on two commonly used plastic polymers in marine aquaculture: polyamide (PA) and high-density polyethylene (PE). Both untreated and color-additive treated polymers were tested for their response to fouling development. Performance was gauged by total fouling wet weight and the extent of fouling-induced mesh occlusion. Experimental panels were deployed for 4 months (from May to September 2021) in estuarine (oyster farm) and marine (port) environments on the northern coast of Portugal. The marine sites exhibited greater fouling species diversity, while higher biofouling loads were found in the subtidal estuarine area. Within 3 months, complete mesh occlusion occurred mainly due to colonial hydroids (Obelia dichotoma) in the subtidal site. In contrast, panels deployed in the intertidal estuarine area had lower fouling biomass and mesh occlusion. Notably, significant differences between polymer types and treatments were only evident in the estuarine intertidal area, with long air exposure during low tide. White panels outperformed orange ones in fouling biomass, and PA panels outperformed PE panels in mesh occlusion. These differences were attributed to the settlement and growth of the acorn barnacle Austrominius modestus, known to favor dark-colored and less hydrophilic surfaces. Considering that oyster production in intertidal areas is one of the most important aquaculture industries globally, these findings offer valuable insights into material selection and characteristics that can mitigate fouling loads and their associated impacts. These results could also be relevant for other forms of bivalve aquaculture where infrastructure-related biofouling presents a challenge.